Strategi Manajemen Pengembangan Tanaman Beluntas Sebagai Sumber Nutrisi Alami untuk Meningkatkan Nilai Ekonomi dan Daya Saing - Allgis Ravanail; Yusril Nawawi; Via Sumelda; Rahmawati S. Busa; Nadiya Restu Fauziyah; Muhammad Taufik Azhar; Edgina Salsyabila Anindya; Bagas Yuzha Prayoga; Asep Kurniawan; Itto Turyandi (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze management strategies for the development of beluntas as a natural source of nutrients to enhance economic value and competitiveness based on local resources. The study employs a non-empirical approach using a conceptual-qualitative method through a systematic literature review of scientific journals, policy documents, and academic publications related to herbal plants and strategic management. The analysis results indicate that beluntas contains flavonoids, phenolics, and antioxidants that hold potential for development as a value-added functional food commodity. Development barriers include low product innovation, weak managerial capacity, limited branding, and insufficient digital marketing. Strategies based on public education, product diversification, digital branding, and business partnerships are considered capable of enhancing the competitiveness of beluntas while supporting the strengthening of a biodiversity-based local economy.